Changes in the serum metabolomics of polycystic ovary syndrome before and after compound oral contraceptive treatment - Zhao, Ting; Xiao, Xiao; Li, Lingchuan; Zhu, Jing; He, Wenli; Zhang, Qiong; Wu, Jiaqi; Wu, Xiaomei; Yuan, Tao (Frontiers in Endocrinology, 2024)
Background: Polycystic ovary syndrome (PCOS) is both a common endocrine syndrome and a metabolic disorder that results in harm to the reproductive system and whole-body metabolism. This study aimed to investigate differences in the serum metabolic profiles of patients with PCOS compared with healthy controls, in addition to investigating the effects of compound oral contraceptive (COC) treatment in patients with PCOS.Materials and methods: 50 patients with PCOS and 50 sex-matched healthy controls were recruited. Patients with PCOS received three cycles of self-administered COC treatment. Clinical characteristics were recorded, and the laboratory biochemical data were detected. We utilized ultra-performance liquid chromatography-high-resolution mass spectrometry to study the serum metabolic changes between patients with PCOS, patients with PCOS following COC treatment, and healthy controls.Result: Patients with PCOS who received COC treatment showed significant improvements in serum sex hormone levels, a reduction in luteinising hormone levels, and a significant reduction in the levels of biologically active free testosterone in the blood. Differential metabolite correlation analysis revealed differences between PCOS and healthy control groups in N-tetradecanamide, hexadecanamide, 10E,12Z-octadecadienoic acid, and 13-HOTrE(r); after 3 months of COC treatment, there were significant differences in benzoic acid, organic acid, and phenolamides. Using gas chromatography-mass spectrometry to analyse blood serum in each group, the characteristic changes in PCOS were metabolic disorders of amino acids, carbohydrates, and purines, with significant changes in the levels of total cholesterol, uric acid, phenylalanine, aspartic acid, and glutamate.Following COC treatment, improvements in sex hormone levels, endocrine factor levels, and metabolic levels were better than in the group of PCOS patients receiving no COC treatment, indicating that COC treatment for PCOS could effectively regulate the levels of sex hormones, endocrine factors, and serum metabolic profiles.